1995
DOI: 10.1002/jbm.820290908
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐bonding behavior under load‐bearing conditions of an alumina ceramic implant incorporating beads coated with glass–ceramic containing apatite and wollastonite

Abstract: Alumina ceramic with a porous surface coated with glass-ceramic containing apatite and wollastonite (AW-GC) was implanted in a state of press-fit under load-bearing conditions in the femoral condylus of the mongrel dog and compared with a non-glass-ceramic-coated alumina ceramic. A trapezoid alumina ceramic implant (7 x 10 x 5 mm) with a lateral recess (0.9 mm deep) coated with alumina ceramic beads (mean diameter, 750 microns) in a single layer was prepared. The alumina ceramic beads were bonded to the alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Alumina ceramics, which have mainly been ␣-alumina, are known to have favorable characteristics such as good biocompatibility, high mechanical-strength, high resistance to fatigue, and good lubrication properties, but are also known to be bioinert in its bulk form since it does not bond directly with the bone without surface modification. 15,23 The results of the present study indicate that ABC has excellent osteoconductive ability.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Alumina ceramics, which have mainly been ␣-alumina, are known to have favorable characteristics such as good biocompatibility, high mechanical-strength, high resistance to fatigue, and good lubrication properties, but are also known to be bioinert in its bulk form since it does not bond directly with the bone without surface modification. 15,23 The results of the present study indicate that ABC has excellent osteoconductive ability.…”
Section: Discussionmentioning
confidence: 79%
“…14 Alumina ceramics have good biocompatibility, high mechanical-strength, high resistance to fatigue, and excellent lubrication properties. 15 They are now used clinically for prosthetic implants such as total hip 16 and knee 17 prostheses. However, alumina ceramics are bioinert and have no bone-bonding ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Alumina ceramics have good biocompatibility, high mechanical strength, high resistance to fatigue, and excellent lubrication properties. 15 They are used clinically for prosthetic implants such as total hip 16 and knee 17 prostheses. However, alumina ceramics are bioinert and have no bone-bonding ability.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, attempts have been made to improve the bone-bonding strength, mainly by surface modification. 15,[18][19][20] Kobayashi et al reported a new composite consisting of a Bis-GMA-based resin as an organic matrix and alumina bead powder, produced by fusing ␣-alumina powder and subsequently quenching it as an inorganic filler. 21 They showed that this alumina bead composite has excellent osteoconductivity.…”
Section: Introductionmentioning
confidence: 99%